Value of N-Terminal Pro-Brain Natriuretic Peptide for Embolic Events Risk Prediction in Patients with Atrial Fibrillation; a Systematic Review and Meta-Analysis - Ahmadzadeh, Koohyar; Hajebi, Amirali; Ramawad, Hamzah Adel; Azizi, Yaser; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2023)
Introduction: A comprehensive conclusion has yet to be made about the predictive value of serum N-terminal pro-brain natriuretic peptide (NT-proBNP) for stroke/systemic embolic events (SEE) in patients with atrial fibrillation (AF). This study aims to review the evidence for evaluating the value of NT-proBNP in predicting the risk of stroke/SEE in patients with AF through a systematic review and meta-analysis. Method: Two independent reviewers screened all relevant studies that were retrieved from the database of Medline, Embase, Scopus, and Web of Science until December 7th, 2021. The predictive value of NT-proBNP in the prediction of stroke/SEE was recorded as hazard ratio (HR) and 95% confidence interval (95% CI). Results: Nine articles (38,093 patients, 3.10% stroke/SEE) were included in our analysis. There was no publication bias in these studies (P=0.320). Our analysis showed that NT-proBNP can be a good predictor of stroke/SEE risk in AF patients, even at different cut-off values (HR=1.76; 95% CI: 1.51, 2.02; P < 0.001). Subgroup analysis showed that diabetes could have a possible effect on the predictive value of NT-proBNP (meta-regression coefficient = 0.042; P = 0.037). Conclusion: Measurement of NT-proBNP during the first admission could be used to assess the short- or long-term risk of stroke/SEE in patients with AF. Further studies are needed to evaluate the possible applicability of serum NT-proBNP measurement in the settings in which stroke is the sole outcome of the investigation.